Challenges in IgA Nephropathy Management: An Era of Complement Inhibition - Tesař, Vladimir; Radhakrishnan, Jai; Charu, Vivek; Barratt, Jonathan (Kidney international reports, 2023)
IgA nephropathy (IgAN) is the most common glomerular disease worldwide, with an estimated annual incidence of 25 per million adults. Despite optimized supportive care, some patients fail to achieve disease control and suffer progressive deterioration of kidney function. In this subpopulation of patients, the Kidney Disease: Improving Global Outcomes 2021 guidelines recommend consideration of corticosteroids; however, their use is associated with significant side effects. Ongoing clinical trials are expected to identify corticosteroid-sparing therapies to help improve treatment and prognosis for patients with IgAN. It has been well-documented that the complement system plays a significant role in IgAN pathogenesis, and several complement inhibitors are now entering late-stage clinical development. This review evaluates what we know about the role of complement in the pathophysiology of IgAN and considers how the availability of targeted complement inhibitors may impact future clinical practice. Key knowledge gaps are evaluated, and research opportunities are recommended to help guide clinical decision-making and optimize patient outcomes. Such gaps include evaluating the relative contribution of the alternative and lectin pathways to disease pathogenesis, and the importance of determining the dominant pathway driving IgAN progression. Continued research into the staining of complement proteins in kidney biopsies and identifying targeted biomarkers to assess disease progression and treatment responses will also be needed to support the implementation of newer therapies in clinical practice. Considering the future horizons for enhancing the care of patients with IgAN, tackling the outstanding challenges now will help prepare for the best possible future outcomes.
Keywords: biomarkers; alternative pathway; complement inhibition; lectin pathway; clinical trials; IgA nephropathy